The Existence of Victims in the Implementation of Diversion in the Resolution of Criminal Acts Committed by Children - Rabbani, Najmi; Wulandari, Cahya (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Indonesia's juvenile justice system faces significant challenges in implementing diversion mechanisms that marginalize victim existence. The assault case involving seven motorcycle-riding juveniles in Tasikmalaya demonstrates substantial gaps between normative guarantees and restorative justice practices that predominantly focus on offenders rather than victims' needs and participation.Purposes of the Research: This study examines victim existence in diversion efforts within Indonesia's juvenile criminal justice system and analyzes factors influencing restorative justice implementation. The research aims to identify structural barriers preventing meaningful victim participation in juvenile diversion processes.Methods of the Research: The research employs qualitative juridical-empirical methodology through semi-structured interviews with prosecutors and legal document analysis. This approach enables comprehensive examination of diversion practices in concrete cases, revealing implementation gaps in restorative justice frameworks.Results Main Findings of the Research: Findings reveal that diversion processes remain dominated by offender-oriented approaches, systematically marginalizing victim participation and recovery needs. Despite Article 6 of Law Number 31/2014 guaranteeing psychosocial rehabilitation for victims, adult victims receive inadequate support compared to child victims. The Tasikmalaya case, involving collective revenge motives, resulted in Rp75 million compensation from Rp120 million total medical costs. Inhibiting factors include structural-institutional limitations, socio-cultural resistance, and psychological-participatory challenges. Achieving meaningful victim existence requires structural reforms integrating victimological approaches, prioritizing measurable recovery mechanisms, and strengthening institutional capacity for substantive victim participation while maintaining child welfare principles.